(untitled) (Contemporary Journal of Social Science Review, 2024)
Quality management is an important tool to maintain all sort of standards in educational institution. The major objective of this research was to investigate the perception of secondary school students regarding service quality management. The population of the study was public and private secondary school students from Hafizabad whereas, 300 (Public= 154, Private= 146) respondents were selected as sample of this study through simple random sampling technique. The study was quantitative based on the casual comparative research design therefore, a structured questionnaire was administered to collect the primary data from the respondents through survey method. The Statistical Package for Social Sciences (SPSS) was administered to analyze the research questions. The findings of the study showed that both public and private schools have strengths in different areas of service quality. Private schools generally provide higher levels of student satisfaction, particularly in terms of reliability, responsiveness and empathy. The findings highlighted the need for public schools to improve their responsiveness and safety measures to meet students’ expectations better. Evaluating service quality in secondary schools through educators’ satisfaction carries important implications for strategic planning. The proposed measurement scale can be adapted by other secondary schools to monitor their progress and assess internal service quality for ongoing improvement.